2020
DOI: 10.1093/geront/gnz192
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Loneliness: Why Do First-Generation Migrants Feel More Lonely Than Their Native Dutch Counterparts?

Abstract: Background and Objectives Along with the current aging demographics in the Netherlands, the number of older first-generation migrants is also increasing. Despite studies suggesting a higher quantity of social contacts of migrants, loneliness is more common among migrants as compared to native Dutch. We theorize that migrants experience more emotional and social loneliness due to a lower satisfaction with social relationships and lower participation in social activities, respectively, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…Neither could we pay any attention to differences between the categories of origin with respect to their views on the priority they give to their individual goals versus those of the collective they are part of. Dutch culture was already highly individualistic decades ago compared to Morocco and Turkey (Hofstede 1983), and this may mean that older Dutch adults have different expectations and are less likely to feel lonely than older Moroccans and Turks (Swader 2019). The present study therefore gives a very limited view on cross-cultural factors in loneliness and has a limited view on the diversity within the three origin categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither could we pay any attention to differences between the categories of origin with respect to their views on the priority they give to their individual goals versus those of the collective they are part of. Dutch culture was already highly individualistic decades ago compared to Morocco and Turkey (Hofstede 1983), and this may mean that older Dutch adults have different expectations and are less likely to feel lonely than older Moroccans and Turks (Swader 2019). The present study therefore gives a very limited view on cross-cultural factors in loneliness and has a limited view on the diversity within the three origin categories.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (Visser and el Fakiri 2016 ) did examine the significance for loneliness of a partner relationship and contact with neighbours, but not the significance of other types of social relationships. Another Dutch study (ten Kate et al 2020 ) among middle-aged and older non-Western migrants from five different countries together showed that their lower relationship satisfaction compared to Dutch people was related to higher loneliness. Relationship satisfaction, however, is conceptually close to loneliness, and relationship content was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Even when the children meet their parents’ expectations, this does not guarantee harmonious relationships. While prior research has shown that overall relationship satisfaction reduces loneliness for both older migrants and non-migrants (De Jong Gierveld et al 2015 ; Kim 1999 ; Ten Kate et al 2020 ), little is known about different types of family conflicts and how they affect loneliness in old age.…”
Section: Lonely While Not Alonementioning
confidence: 99%
“…Yet it is remarkable and regrettable that so little attention is paid to older migrants, as they are generally considered particularly vulnerable and may be in double (Dowd and Bengtson 1978 ) or even triple jeopardy (Norman 1985 ). The few studies that included older migrants indeed show that, on average, they are at greater risk of loneliness than older adults without a migration background (Fokkema and Naderi 2013 ; Lin et al 2016 ; Ten Kate et al 2020 ; Uysal-Bozkir et al 2017 ; Wu and Penning 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, adult education institutions can play an important role, particularly for fostering social networks, since they bridge different societal groups (Healy 2001) and therefore act as a meeting place for people. Given that immigrants are more likely to be socially isolated (Hao and Johnson 2000;Kate et al 2020) and have smaller social networks compared to natives (Martinovic et al 2009), they may therefore benefit to a higher extent from ALE participation.…”
Section: Swb and Educationmentioning
confidence: 99%